Perception of Feedback and Autonomy Among Gynecology Residents During In-Person Versus Telemedicine Clinic - Chan, Kelsi; Olson, Holly; Natavio, Melissa; Stowers, Paris N. (International medical education, 2025)
Over the past decade, telehealth provision of care has become increasingly common. This shift away from in-person clinics may impact the experience of medical learners and the preceptors who train them. This study aimed to measure and compare obstetrics and gynecology resident physicians’ perceived quality of educational feedback during telemedicine compared to in-person clinical encounters. This prospective observational study recruited residents enrolled in a family planning clinical rotation at an academic residency program. After every in-person and telemedicine clinic session from January 2021 to February 2022, participating residents were sent a link to a 3 min survey via text message. Ordinal regression modeling was used to compare Likert responses between the telehealth and in-person clinical settings. All nine residents enrolled in the clinical rotation chose to participate in this study and responded to 114 of 132 survey prompts (86%). Participants positively rated the feedback they received during all clinic sessions. When comparing the two clinic experiences, there was no statistically significant difference in perceived quality of feedback or satisfaction with feedback. Residents’ perception of educational feedback during telemedicine clinic is at least similar for most measures and superior for contraception counseling when compared to an in-person clinic.